Operasi Militer Selain Perang dalam Rangka Penanggulangan Bencana Alam di Indonesia: Peluang, Tantangan, dan Studi Komparasi - Fatimah, Fatimah; Rahakbauw, Isro' Kurniawan; Eriyono, Ruben Hisar (Jurnal Kajian Stratejik Ketahanan Nasional, 2023)
Indonesia is a country that is prone to natural disasters in terms of geography and topography. In 2008, the National Disaster Management Agency (BNPB) was formed which functions to coordinate disaster management in Indonesia. BNPB partners with various institutions in Indonesia, one of which is the Indonesian National Armed Forces (TNI). Overcoming disasters is one of the main tasks of the TNI in Military Operations Other Than War (OMSP). This research is quantitative in nature with a literature study to look at opportunities, challenges and comparative studies of OMSP activities in managing natural disasters. In the context of natural disaster management in Indonesia, this research concludes that the involvement of TNI through Military Operations Other Than War (MOOTW) is a significant step in optimizing disaster response efforts. The collaboration between TNI and the BNPB demonstrates a synergy that enhances the country's capacity to respond to natural disasters. However, the study highlights the need for further evaluation of the implementation strategies and challenges faced, given the dynamic changes in disaster patterns. This conclusion underscores the importance of continually improving and developing collaborative strategies to ensure optimal readiness and responsiveness to the challenges of natural disasters in the future.